Antiferromagnetic coupling between Mn3+ and Mn2+ cations in Mn‐doped spinel ferrites. Issue 12 (19th August 2015) - Xu, J.; Ma, L.; Li, Z. Z.; Lang, L. L.; Qi, W. H.; Tang, G. D.; Wu, L. Q.; Xue, L. C.; Wu, G. H.
Abstract : Ferrite powder samples of Mn x Ni1– x Fe2 O4 (0.0 ≤  x  ≤ 1.0) with single phase (A)[B]2 O4 spinel structure were prepared using a sol–gel method. Following the successful proposal by our group, that the magnetic moment directions of Cr 2+ (3d 4 ) cations are antiparallel to those of Fe 3+ (3d 5 ) and Fe 2+ (3d 6 ) cations in a given sublattice of the Cr‐doped spinel ferrites due to the constraints imposed by Hund's rules, we extend here the same idea and assume that the magnetic moment directions of Mn 3+ (3d 4 ) cations are also antiparallel to those of Mn 2+ (3d 5 ) and divalent and trivalent Fe (Ni) cations in a given sublattice of Mn‐doped spinel ferrites. We have thereby obtained cation distributions for the samples by fitting the magnetic moments of the samples at 10 K. The results indicate that 72% of the Mn cations occupy the [B] sites in MnFe2 O4, which is close to the results for Ni (82%) in NiFe2 O4, but is different from the result obtained using the conventional view which yields 80% of the Mn cations in the (A) sites of MnFe2 O4 . On the basis of the present analyses of the magnetic structure of Mn x Ni1– x Fe2 O4 (0.0 ≤  x  ≤ 1.0), we propose here a new model for spinel ferrites that is distinctly different from both the super‐ and the double‐exchange model and that we refer to as the O2p itinerant electron model. Using this model, not only can the magnetic structure of the spinel ferrites M Fe2 O4 ( M  = Fe, Co, Ni, and Cu) be explained better than by using the super‐ and double‐exchange interaction models, but also the magnetic structure and the cation distributions of Cr‐, Mn‐, and Ti‐doped spinel ferrites can be explained.